Análise dinâmica de vigas de eixo curso e seção aberta submetidas a cargas móveis - Carbonari, Gilberto (Semina: Ciências Exatas e Tecnológicas, 2004)
This work deals with linear analysis of nonsymmetric curved thin-walled bridges or beams with open cross section, with physical properties, geometry and radius of curvature constant along the centroidal axes. VLASOV differential equations where used, considering the coupling between deformations on the vertical, transversal, axial, and torsional directions. Central finite difference method was used to solve the system of four partial differential equations. Bacisally two analysis were performed: DINAMIC and STATIC. Both were also used to obtain the impact coeficcient (C.M.D.). The first analysis refers to the determination of the basic dynamic characteristies (natural frequency and vibration modes), and the determination of the dynamic response of the beam, in stresses and deformations, for arbitrary mobile loads. Beams with any combination of the boundary conditions, including pinned or fixed ends on the three directions of torsion and bending were considered. A comparison between the results of the theoretical analysis, produced by computer programs implemented in a microcomputer (for the static analysis) and computer B-6700 (for the dynamic analysis), and the ones given in the references and also obtained experimentally. Showed a good correlation.